Determining factors of university evasion: An analysis with UNISINOS students - Furtado, Vanessa Viégas Alves; Alves, Tiago Wickstrom (Contextus - Revista Contemporânea de Economia e Gestão, 2023)
This work aims to conduct an analysis of the determinants of university dropout from the University of the Bells River Valley (UNISINOS). The study was conducted from a representative sample of students in UNISINOS, entrants in the period from 2005 to 2008, and evaluated by Logit regression of the relationship between socioeconomic variables and dropout students. It was concluded that some of the variables had increased relative to the avoidance, for example, the variable subjects canceled, wherein a greater number of cancellations resulted in a higher probability of escaping. Like others who had inverse relation to this phenomenon, as the variable subjects taken, in which a greater number of courses taken per semester, reduced the chances of evading student.